Evaluasi Aplikasi Sistem Informasi Manajemen Akuntansi Barang Milik Negara (Simak Bmn) Kaitannya Dalam Pencatatan Nilai Aset Tetap Pemerintah Studi Kasus pada Pusat Penelitian dan Pengembangan Tanaman Pangan Bogor - Pamungkas, Bambang; Fatchudin, Fatchudin; Kusumahdinata, Agung (Jurnal Ilmiah Ranggagading (JIR), 2011)
One concrete effort by government to achieve transparency and accountability in managing the state budget (APBN/APBD) is delivery of government financial reporting that meets the principles of timely and prepared to follow governmental accounting standard which have been generally accepted. It is stipulated in law No 17 of 2003 on state finance, which requires the form and content of execution accountability reports APBN/APBD are prepared and presented according to government accounting standard. And explanation of Law No 1 year 2004 regarding state treasury stating that information presented in governmental financial reports can fulfill the principle of timely need to be held in Accounting System Central Government (SAPP), which consists of the central Accounting System (SiAP) and the Agency Accounting System (SAI). SAI consists of Financial Accounting System (GAAP) and the Accounting System State Property Goods (SABMN). Accounting Management Information System, hereinafter abbreviated to SIMAK is a financial application based on the financial accounting system (SAK). Meanwhile, SIMAK Application of State Property Goods (BMN) based on the Accounting System of State Property Goods (SABMN) held with the aim to produce the required information as a tool of accountability for the implementation of APBN and Management/control BMN used by a user of accounting unit goods. The aim study is to find out how the application procedure SIMAK BMN whether has helped the acceleration of accountability and transparency in the management of government fixed asset, and what are the outputs and the barriers that occur when implementing these procedures. For it is necessary for evaluation application system management accounting of state property goods (SIMAK BMN) related in listing of government fixed asset value starts at the smallest entity that began in the work unit level accounting unit power user stuff (UAKPB). Therefore, the research conducted on unit of work done on research and development center of food crops (Puslitbangtan) Bogor, which is a UAKPB unit under the ministry of agriculture. Evaluation results show that the application can be helpful for transparency and accountability in the management of government assets if managed properly. its just that there are some constraints on the arrangement of BMN particularly frequent transfer of chattels which are not reported to the person in charge of the room. Consequently BMN records are inaccurate.